2017
DOI: 10.1302/2046-3758.610.bjr-2017-0170
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the PROFHER trial findings on surgeons’ clinical practice

Abstract: ObjectivesTo explore whether orthopaedic surgeons have adopted the Proximal Fracture of the Humerus: Evaluation by Randomisation (PROFHER) trial results routinely into clinical practice.MethodsA questionnaire was piloted with six orthopaedic surgeons using a ‘think aloud’ process. The final questionnaire contained 29 items and was distributed online to surgeon members of the British Orthopaedic Association and British Elbow and Shoulder Society. Descriptive statistics summarised the sample characteristics and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…RCTs have an influence on medical practice as demonstrated with the PROFHER study. In it, half of the surgeons stated that they did fewer operations on PROFHER-eligible fractures after the publication of the PROFHER study in response to an online questionnaire via emails through the British Orthopedic Association [5]. Nevertheless, a randomized study demonstrated that opinion leaders influence the medical community to implement practice guidelines more effectively than audits and feedback [1].…”
Section: Discussionmentioning
confidence: 99%
“…RCTs have an influence on medical practice as demonstrated with the PROFHER study. In it, half of the surgeons stated that they did fewer operations on PROFHER-eligible fractures after the publication of the PROFHER study in response to an online questionnaire via emails through the British Orthopedic Association [5]. Nevertheless, a randomized study demonstrated that opinion leaders influence the medical community to implement practice guidelines more effectively than audits and feedback [1].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there has been a cultural shift in orthopedic surgery with a growing number of successful randomized clinical trials that have reduced uncertainty and influenced both practice and policy. [7][8][9][10][11][12] However, this has predominately involved adult orthopaedic surgery and is yet to be realized within children's orthopaedics.…”
Section: Cite This Article: Bone Joint J 2018;100-b:680-4mentioning
confidence: 99%
“…Several studies are starting to quantify the change in orthopaedic clinical practice following published level 1 evidence. Early attempts include the distal radius acute fracture fixation trial12 and proximal fracture of the humerus: evaluation by randomisation (PROFHER)13 randomised control trials. A review of the English Hospital Episode Statistics demonstrated that surgeons appeared to change their practice pattern for distal radius fractures after a large randomised control trial.…”
Section: Introductionmentioning
confidence: 99%